Wege der Erreichbarkeit sozioökonomisch benachteiligter Familien Ein umsetzungsorientierter Dialog zwischen Forschung und Praxis in der Suchtprävention - Pfister, Andreas (Seismo, 2023)
Children in socio-economically deprived families are at a higher risk of developing addiction problems later on. Nevertheless, these families are hardly reached by health promotion and prevention. What are the reasons for this? How can actors in practice and politics change this? This book shows that socio-economically deprived families are a heterogeneous group. Increased intersectoral cooperation between health and social services can improve accessibility. The greatest leverage lies in raising the social situation and living conditions of these families. Attention must also be paid to the different ways in which families seek (health) information and the strategies they use to protect themselves from stigmatisation. Experts and politicians reflect on the results of the study and classify them. In this way, a dialogue between research and practice shows which strategies can be used to ensure addiction prevention and health promotion for socio-economically deprived families at addiction prevention centres, in the school and leisure sector, in social services and in social and health policy.